2019
DOI: 10.1042/bsr20182476
|View full text |Cite|
|
Sign up to set email alerts
|

PAR-2 promotes cell proliferation, migration, and invasion through activating PI3K/AKT signaling pathway in oral squamous cell carcinoma

Abstract: Objective: This research aimed to explore the function of protease activated receptor 2 (PAR-2) in oral squamous cell carcinoma (OSCC) development and progression, as well as underlying molecular mechanism. Methods: Tissue samples were collected from 115 OSCC patients. Quantitative real-time PCR (qRT-PCR) was performed to measure the expression of PAR-2 mRNA in OSCC tissues and cells. MTT and Transwell assays were used to detect the proliferation, migration, and invasion of OSCC cells, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…21,22 The levels of P-PI3K and P-AKT are vital indicators of the activity of the PI3K/AKT signaling pathway, which is associated with aggressive tumor cell behaviors in OSCC, such as proliferation, angiogenesis, metastasis, and chemoresistance. [23][24][25] Interestingly, we found that P-PI3K and P-AKT levels were predominantly weakened in SCC-4…”
Section: Discussionmentioning
confidence: 72%
“…21,22 The levels of P-PI3K and P-AKT are vital indicators of the activity of the PI3K/AKT signaling pathway, which is associated with aggressive tumor cell behaviors in OSCC, such as proliferation, angiogenesis, metastasis, and chemoresistance. [23][24][25] Interestingly, we found that P-PI3K and P-AKT levels were predominantly weakened in SCC-4…”
Section: Discussionmentioning
confidence: 72%
“…The PI3K/AKT signaling pathway is related to a variety of human malignant tumor biological processes, such as cell adhesion, growth, invasion, and angiogenesis (34,35). The PI3K/AKT pathway is one of the most common activation pathways in cancers, and it is of great significance in regulating glucose metabolism, proliferation and apoptosis of tumor cells (36). Akt plays a role in the anti-apoptotic pathway through phosphorylation of downstream target proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The PARs are a family of G-Protein coupled Receptors that are often described as coagulation sensors, since their mode of action includes a proteolysis step induced by thrombin or other coagulation proteases. The expression of PAR2 was recently reported to transduce mitogenic and proinvasive signals in OSCC cells [ 27 , 28 ]. The activation of PAR2 may directly boost tumor growth after surgery.…”
Section: Key Perioperative Events and The Relevant Biological Parametersmentioning
confidence: 99%